Knowledge Integration in the Islamic Religious Education Study Program at STAIN Sultan Abdurrahman Kepulauan Riau - Arham Junaidi Firman; Maragustam Siregar; Muqowim Muqowim; Zaharuddin M; Abdul Majir; Ona Yulita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research is motivated by the implementation of knowledge integration within the Islamic Religious Education Study Program at STAIN Sultan Abdurrahman, aiming to address the issue of dichotomy and the trend of knowledge development that leads to multi, inter, and transdisciplinary approaches. The research aims to analyze the implementation of knowledge integration in the Islamic Religious Education Study Program at STAIN Sultan Abdurrahman Kepulauan Riau. Employing a qualitative research design with an interpretative approach, the research subjects include the chairperson, secretary, and lecturers of the Islamic Religious Education Study Program at STAIN Sultan Abdurrahman Kepulauan Riau. Data collection is conducted through interviews, observations, and documentation. Data analysis is carried out descriptively with stages of condensation, display, conclusion drawing, and verification. The research findings reveal the following: Firstly, the rationale behind the implementation of knowledge integration is evident across multiple levels. At the paradigmatic level, this commitment is observed through the integration of knowledge via the program's vision, mission, and motto. The policy level is enacted through leadership regulations, while at the program level, implementation occurs solely through seminars hosted by STAIN Sultan Abdurrahman Kepulauan Riau. Notably, the Islamic Religious Education Study Program has not pursued comparable endeavors. Secondly, the implementation of knowledge integration is discerned through its practical implementation in education and teaching. However, a comprehensive analysis demonstrates that aspects of planning, execution, and learning assessment have yet to encompass the philosophical, material, methodological, and evaluative levels.